IMPLEMENTASI PENERAPAN HUMAN CENTERED DESIGN (HCD) PADA IMUNISASI DASAR DI WILAYAH PUSKESMAS TAMBAKREJO DUSUN PETENGAN DESA TAMBAKREJO KABUPATEN JOMBANG - Dian Puspita Yani,; Siti Roudhotul Jannah,; Suyati, Suyati; Muzayyaroh, Muzayyaroh; Sri Banun Titi Istiqomah, (Journal of Innovation Research and Knowledge, 2025)
Background: The immunization program in Indonesia, which is still being promoted by the Indonesian government, aims to continue reducing infant and child mortality rates. However, the program appears to still be facing problems, namely parental refusal. This refusal is caused by public misunderstandings about immunization, a lack of education, and a lack of knowledge and awareness about it. This study applies Human Centered Design (HCD) approach to understand mothers' perspectives who refuse immunization for their children. Methods: A qualitative study using in-depth interviews with mothers who refused complete basic immunization for their children aged 0-24 months. Data were analyzed thematically following HCD principles. Results: Six main themes emerged: (1) Deep-rooted beliefs and convictions, (2) Excessive fears and concerns, (3) Negative experiences with health services. Conclusion: Vaccine refusal is a complex. HCD approach reveals that mothers' decisions are "rational" within their value systems. Interventions must be multi-level, involving religious leaders, improving health service quality, and enhancing communication between healthcare providers and mothers